2015
DOI: 10.3390/ijms16036183
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage: A Sensible Mediator of the Differentiation Decision in Hematopoietic Stem Cells and in Leukemia

Abstract: In the adult, the source of functionally diverse, mature blood cells are hematopoietic stem cells, a rare population of quiescent cells that reside in the bone marrow niche. Like stem cells in other tissues, hematopoietic stem cells are defined by their ability to self-renew, in order to maintain the stem cell population for the lifetime of the organism, and to differentiate, in order to give rise to the multiple lineages of the hematopoietic system. In recent years, increasing evidence has suggested a role fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 109 publications
0
24
0
Order By: Relevance
“…Notwithstanding the widely recognized role of DDR as an anticancer barrier by way of its capacity to prevent oncogene-induced replication stress and malignant transformation of precancerous lesions [33], recent findings with bone-marrow myeloid cells expressing the MLL-AF9 fusion oncogene, whose leukemogenic effect reflects its capacity to sustain a differentiation block, show that inhibition of the DDR pathway components ATM, ATR, or Brca1 promotes loss of MLL-AF9 blasts and terminal differentiation, strongly supporting the hypothesis that in some developing malignancies, the DDR might act as an oncogenic driver [34,35]. In addition, these findings suggest that DDR inhibitors may act as differentiation therapy for the treatment of certain myeloid leukemias.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 79%
“…Notwithstanding the widely recognized role of DDR as an anticancer barrier by way of its capacity to prevent oncogene-induced replication stress and malignant transformation of precancerous lesions [33], recent findings with bone-marrow myeloid cells expressing the MLL-AF9 fusion oncogene, whose leukemogenic effect reflects its capacity to sustain a differentiation block, show that inhibition of the DDR pathway components ATM, ATR, or Brca1 promotes loss of MLL-AF9 blasts and terminal differentiation, strongly supporting the hypothesis that in some developing malignancies, the DDR might act as an oncogenic driver [34,35]. In addition, these findings suggest that DDR inhibitors may act as differentiation therapy for the treatment of certain myeloid leukemias.…”
Section: The Essential Function Of Ddr In the Maintenance Of Hscsmentioning
confidence: 79%
“…HSCs must maintain themselves at a relatively constant number throughout life by precisely balancing self-renewal and differentiation [2][3][4]. Most HSCs cycle infrequently and primarily reside in the G0 phase in the hypoxic bone marrow (BM) niche under homeostatic conditions [2].…”
Section: Introductionmentioning
confidence: 99%
“…We can speculate only with potential mechanisms, such as induction of oxidative stress in HSPCs, as DNA is highly susceptible to oxidative damage and can result in single and double strand breaks. Besides, it not clearly understood what drives damaged HSPCs to initiate DNA repair systems and when to enter the cell cycle or to keep quiescent accumulating genotoxic stress (Weiss and Ito, 2015). While, regulatory studies have consistently found lack of genotoxic effects of pesticides in many test systems, there are studies in the open literature supporting genotoxicity by using different biomarkers.…”
Section: Uncertainties and Inconsistenciesmentioning
confidence: 98%
“…This escape mechanism fails when haematopoietic stem cells chose DNA repair by NHEJ over differentiation, in order to maintain their self-renewal, thus thriving haematological malignancies (Weiss and Ito, 2015).…”
Section: Regulatory Relevance Of the Aomentioning
confidence: 99%